2015
DOI: 10.1515/hsz-2014-0261
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride improves the efficiency of induced pluripotent stem cell-derived neurospheres

Abstract: Induced pluripotent stem cell (iPSC)-derived neurospheres, which consist mainly of neural progenitors, are considered to be a good source of neural cells for transplantation in regenerative medicine. In this study, we have used lithium chloride, which is known to be a neuroprotective agent, in an iPSC-derived neurosphere model, and examined both the formation rate and size of the neurospheres as well as the proliferative and apoptotic status of their contents. Our results showed that lithium enhanced the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…2B ). These data support previous studies where lithium was found to increase neurosphere growth in vitro , hence ruling out the possibility that this treatment may be sensitizing NSPCs in the developing brain to irradiation [ 36 , 61 ]. Lithium has previously been observed to radio-sensitize cancerous cells and at the same time protect NSPCs, possibly due to lithium acting on genes with multifunctional roles in distinct DNA repair pathways, which are frequently aberrant in cancer [ 35 , 62 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2B ). These data support previous studies where lithium was found to increase neurosphere growth in vitro , hence ruling out the possibility that this treatment may be sensitizing NSPCs in the developing brain to irradiation [ 36 , 61 ]. Lithium has previously been observed to radio-sensitize cancerous cells and at the same time protect NSPCs, possibly due to lithium acting on genes with multifunctional roles in distinct DNA repair pathways, which are frequently aberrant in cancer [ 35 , 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with previous studies, we found that lithium, applied as a pre-treatment and maintained after irradiation, moderately decreased DNA damage (γH2AX) and recruited a significant proportion of NSPCs into proliferation [ 31 ]. However, in contrast to previous reports we did not find any evidence of lithium preventing young NSPCs from irradiation-induced apoptosis, as judged by annexin V and Sub-G 1 cell cycle analysis [ 34 , 36 ].…”
Section: Introductioncontrasting
confidence: 99%
“…Recently, an efficient and simple method to induce the stem cell differentiation was reported. Lithium (Li), the smallest alkali metal with an atomic weight of 6.9, was found to enhance the efficiency of induced pluripotent stem cell-derived neurospheres (Tafreshi et al 2015), promote the odontoblast differentiation of hair follicle neural crest cells (Shan et al 2015), modulate the proliferation and differentiation of mesenchymal stem cells (Dong et al 2015;Tang et al 2015), prevent neural progenitor cell apoptosis (Cabrera et al 2014). These studies indicated that Lithium may play function in the NSCs' differentiation.…”
Section: Introductionmentioning
confidence: 99%